Two mental models of integrated care for advanced liver disease: qualitative study of multidisciplinary health professionals. Issue 9 (5th September 2022) - Arney, Jennifer; Gray, Caroline; Walling, Anne M; Clark, Jack A; Smith, Donna; Melcher, Jennifer; Asch, Steven; Kanwal, Fasiha; Naik, Aanand D
Abstract : Objectives: The purpose of this paper is to present two divergent mental models of integrated advanced liver disease (AdvLD) care among 26 providers who treat patients with AdvLD. Setting: 3 geographically dispersed United States Veterans Health Administration health systems. Participants: 26 professionals (20 women and 6 men) participated, including 9 (34.6%) gastroenterology, hepatology, and transplant physicians, 2 (7.7%) physician assistants, 7 (27%) nurses and nurse practitioners, 3 (11.5%) social workers and psychologists, 4 (15.4%) palliative care providers and 1 (3.8%) pharmacist. Main outcome measures: We conducted qualitative in-depth interviews of providers caring for patients with AdvLD. We used framework analysis to identify two divergent mental models of integrated AdvLD care. These models vary in timing of initiating various constituents of care, philosophy of integration, and supports and resources needed to achieve each model. Results: Clinicians described integrated care as an approach that incorporates elements of curative care, symptom and supportive care, advance care planning and end-of-life services from a multidisciplinary team. Analysis revealed two mental models that varied in how and when these constituents are delivered. One mental model involves sequential transitions between constituents of care, and the second mental model involves synchronous application of the various constituents. Participants described elements of teamwork and coordination supports necessary to achieve integrated AdvLD care. Many discussed the importance of having a multidisciplinary team integrating supportive care, symptom management and palliative care with liver disease care. Conclusions: Health professionals agree on the constituents of integrated AdvLD care but describe two competing mental models of how these constituents are integrated. Health systems can promote integrated care by assembling multidisciplinary teams, and providing teamwork and coordination supports, and training that facilitates patient-centred AdvLD care.